Penghargaan dan sanksi terhadap kinerja karyawan PT. Agung Toyota Cabang Pangkalan Kerinci - Supriyadi, Agus (Jurnal Paradigma Ekonomika, 2021)
Human resources play a critical part in accomplishing a company's aims and goals. Efforts to recruit professional individuals are inextricably linked to how leaders manage their human resources to meet organizational objectives as a company engaged in selling various series cars, PT. Agung Toyota Pangkalan Kerinci Branch has been committed to delivering incentives and punishments to its personnel in its activities. In actuality, the company's product sales target has been decreasing year after year. As a result, this research aimed to see if coupling Reward and Punishment had a substantial impact on staff performance at the PT. Agung Toyota Pangkalan Kerinci Branch. The study followed a quantitative approach, utilizing multiple linear regression analysis to determine the effect. Questionnaires and interviews were undertaken to acquire primary data, and some extra data was used as preliminary data. According to the findings, rewards have a considerable impact on employee performance, and punishment has a significant effect on employee performance. Â